Step-by-step explanation:
tan⁻¹(x) = ∑ₙ₌₀°° (-1)ⁿ x²ⁿ⁺¹ / (2n+1)
tan⁻¹(1/√3) = ∑ₙ₌₀°° (-1)ⁿ (1/√3)²ⁿ⁺¹ / (2n+1)
tan⁻¹(1/√3) = ∑ₙ₌₀°° (-1)ⁿ (1/√3) (1/√3)²ⁿ / (2n+1)
tan⁻¹(1/√3) = (1/√3) ∑ₙ₌₀°° (-1)ⁿ (1/3)ⁿ / (2n+1)
π/6 = (1/√3) ∑ₙ₌₀°° (-1)ⁿ (1/3)ⁿ / (2n+1)
π = (6/√3) ∑ₙ₌₀°° (-1)ⁿ (1/3)ⁿ / (2n+1)
π = 2√3 ∑ₙ₌₀°° (-1)ⁿ / (3ⁿ (2n+1))
Answer:
A
Step-by-step explanation:
Given the 2 equations
x = 3 - y → (1)
5x - 12 = y → (2)
Substitute x = 3 - y into (2)
5(3 - y) - 12 = y ← distribute and simplify left side
15 - 5y - 12 = y
3 - 5y = y ( add 5y to both sides )
3 = 6y ( divide both sides by 6 )
= y, that is
y = 0.5 → A
Step-by-step explanation:
_
0.416666666666666666666
Is this a question? Nine divided by 2.43 is 3.703703703703703703